Drug Utilization Evaluation of Vancomycin in Pediatric Department - Dehghan, Farzaneh; Khorami, Narges; Taslimi Taleghani, Naeeme; Bassiri, Azita; Davoodian, Parivash; Shirvani, Fariba; Zolghadri, Nader; Shoaei, Simin Dokht (Novelty in Biomedicine, 2018)
Background: Increasing reports of Vancomycin resistance have raised concerns about effectiveness of this drug. One of the most important factors of resistance emergence is no adherence of physician to principles of antibiotic therapy. This study is a drug utilization evaluation (DUE) of Vancomycin in pediatric ward to assess appropriateness of drug regimens and to find possible problems in clinical practices that may necessitate reconciliation to improve Vancomycin use. Materials and Methods: This prospective study was done for 1year from October 2014 to September 2015 at Khalij Fars General Hospital in Bandar Abbas. Data including patients’ demographics, paraclinic, diagnosis, vancomycin dose, and treatment duration were collected. The concordance of practice with standard guidelines (CDC, ASHP, and IDSA) and principles of antibiotic therapy was assessed. Results were analyzed by SPSS 20. Results: 102 medical records were reviewed in this study. Pneumonia (60=59%) and sepsis (22=21.5%) were the most common diagnosis. Sampling was done in 6% of patients with 2% antibiogram. Vancomycin was administered appropriately in 56.9% percent of patients with no sex difference (PV= 0.55) but age with significant difference (PV= 0.017). Over use was in a great proportion of patients (36cases=35%) as unnecessary, improper combination and broad spectrum regimen. Conclusion: Vancomycin was overused irrationally in a great proportion of patients. There was no serum level monitoring. Microbial resistance, serum trough level monitoring programs and continuous medical education for physicians can be effective in rational use of antibiotic.